Survival improvements associated with access to biological agents: Results from the South Australian (SA) metastatic colorectal cancer (mCRC) registry. (2nd April 2016) - Tomita, Yoko; Karapetis, Christos S.; Ullah, Shahid; Townsend, Amanda R.; Roder, David; Beeke, Carol; Roy, Amitesh C.; Padbury, Rob; Price, Timothy J.
Abstract: Background Randomized controlled trials evaluating biological therapy have shown improvements in survival from metastatic colorectal cancer (mCRC). Subjects in the trials represent a selected proportion of mCRC patients. We have the potential to assess the impact of biological therapy on mCRC outcomes, particularly the effect of bevacizumab, from a population-based clinical registry by comparing two time cohorts with differences in therapy accessibility. Material and methods A retrospective cohort study was performed by analyzing the South Australian (SA) mCRC registry data based on diagnosis in two time periods: 1 February 2006–31 May 2009 (Cohort A) versus 1 June 2009–30 June 2014 (Cohort B). The demarcation for these cohorts was chosen to reflect the change in accessibility of bevacizumab from July 2009. Results Between February 2006 and June 2014, 3308 patients were identified through the SA mCRC registry: 1464 (44%) in Cohort A and 1844 (56%) in Cohort B. 61 and 59% patients in Cohort A and B, respectively received systemic therapy ( p  = 0.26). Major differences in clinical characteristics were: biological therapy use 18 versus 33% ( p  < 0.001) and clinical trial enrolment 12 versus 7% ( p  < 0.001). Uptake of bevacizumab was: first-line 9 versus 42% and second-line 6 versus 16%. Median overall survival (mOS) for the entire group was: 13.1 versus 17.1 months (HR 0.80; 95% CI 0.74–0.87). Evaluation restricted to patients receiving systemic therapy was 20.5 versus 25.2 months (HR 0.80; 95% CI 0.72–0.89). Multivariate analysis indicated that biological therapy and Cohort B were associated with improved mOS. Conclusion The expected rise in bevacizumab administration was observed in Cohort B. Its use in first-line therapy remained relatively low even after the reimbursement, potentially reflecting real world practice where comorbidities, primary in-situ and age may contraindicate its use. mOS improvement over time was attributed to increased access to biological therapy, especially bevacizumab and possibly advance in peri-operative and supportive care.